Evaluation of solid form and thermodynamic properties for carbamazepine-saccharin (CBZ-SAC) co-crystal - Fatinah, Ab Rahman (2020)
The formation of co-crystal is believed to improve the physicochemical properties of Active Pharmaceutical Ingredients (API). Carbamazepine (CBZ) is a drug that is used as anticonvulsant for treatment of epilepsy and known for having low solubility that can affect the dosage intake in treating patients. It was used as model drug in this study with saccharin (SAC) as co-crystal former. Co-crystallisation of CBZ and SAC was performed to find the co-crystal solid form by varying solvents (ethanol, acetonitrile, ethyl acetate and propanol), crystallisation methods (stirring crystallisation and slurry crystallisation) and SAC/CBZ mol ratio (0.50, 1.00, 1.25, 1.50, 1.75, 2.00, 2.25, 2.50, 2.75 and 3.00). The solubility study and dissolution thermodynamic properties of the co-crystal at various temperatures (25-50 °C) were determined in pure ethanol solution and solution with excess of different SAC ratio. Differential Scanning Calorimetry (DSC), Powder X-Ray Diffraction (PXRD), Fourier Transform Infrared (FTIR) and optical microscopy were used to characterise the co-crystal solid form, while High Performance Liquid Chromatography (HPLC) and synthetic methods were used to determine the solubility of the co-crystal. From the co-crystallisation process, CBZ-SAC co-crystal Form I was successfully formed. SAC/CBZ ratio of 2.25 was chosen as the best ratio since it was the highest ratio that has 100 % conversion of co-crystal. Stirring crystallisation method and ethanol solvent were chosen as the best parameters among others due to CBZ-SAC cocrystal was able to form at higher ratio in this method and pure SAC more soluble in this solvent. Based on the data collected, the co-crystal solubility was found increases as temperature rises for all conditions used. HPLC was chosen as a better method compared to the synthetic as HPLC reported the exact solubility value of the sample tested. The solubility values of co-crystal were compared to be higher than pure CBZ solubility, thus show that the solubility improved with the formation of CBZ-SAC co-crystal at temperatures of 25-50 °C. CBZ-SAC co-crystal ideal solubilities have positive deviation and the experimental co-crystal solubility was correlated well with van’t Hoff model. The thermodynamic properties (ΔsolH0, ΔsolG0 and ΔsolS0) obtained from the apparent thermodynamic analysis have positive values which indicates an endothermic and entropy-driven dissolution of co-crystal in ethanol solvent. The data from this study could amplify the physicochemical properties of CBZ-SAC co-crystal in aqueous solution and the pattern of the CBZ-SAC co-crystal solubility reacting towards temperatures also could be reported. The solubility and physicochemical data from this research could be useful in purification, crystallisation, separation and formulation development of CBZ in pharmaceutical and chemical industries.